2015
DOI: 10.1016/j.numecd.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder, alone or additively with early life adversity, is associated with obesity and cardiometabolic risk

Abstract: Background and Aims There is some evidence that posttraumatic stress disorder (PTSD) and early life adversity may influence metabolic outcomes such as obesity, diabetes, and cardiovascular disease. However, whether and how these interact is not clear. Methods We analyzed data from a cross-sectional and a longitudinal study to determine how PTSD severity influences obesity, insulin sensitivity, and key measures and biomarkers of cardiovascular risk. We then looked at how PTSD and early life adversity may inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 29 publications
2
52
0
5
Order By: Relevance
“…In particular, evidence has shown a strong connection of PTSD with the development of obesity, diabetes, cardiovascular diseases as well as metabolic disease [70][71][72]. On the other hand, ACEs and unpleasant childhood have a profound influence on a person's psycho-social development with regard to personal life styles and habits, paving the way to developing type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, evidence has shown a strong connection of PTSD with the development of obesity, diabetes, cardiovascular diseases as well as metabolic disease [70][71][72]. On the other hand, ACEs and unpleasant childhood have a profound influence on a person's psycho-social development with regard to personal life styles and habits, paving the way to developing type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was the most frequent component of MetS in veterans with PTSD, with the prevalence of alarmingly high 77% (Rosenbaum et al 2015), which was significantly higher for an average prevalence of hypertension in general population of about 40%. In civilian subjects with PTSD, severity of cardiovascular symptoms was positively correlated with body mass index (BMI), waist circumference, fibrinogen, and leptin values, and negatively correlated with insulin sensitivity (Farr et al 2015).…”
Section: Ptsd Mets and Lipid Levelsmentioning
confidence: 99%
“…Several studies reported an association between PTSD and elevated CRP levels (Canetti et al 2014, Farr et al 2015, particularly with re-experiencing CVD and denying symptoms (Canetti et al 2014), and a correlation with CVD manifestations with overall PTSD severity (Farr et al 2015, Michopoulos et al 2015.…”
Section: Ptsd and Crpmentioning
confidence: 99%
“…Fewer studies have investigated associations of trauma and PTSD with endothelial function biomarkers. Although some evidence suggests that PTSD is associated with elevated levels of endothelial cell adhesion molecules that play an early role in the accumulation of lipids within the arterial wall(14), including intercellular adhesion molecule-1 (ICAM-1)(1921) and vascular cell adhesion molecule-1 (VCAM-1)(20), findings have been inconsistent(19,22). …”
Section: Introductionmentioning
confidence: 99%